Recovery of Hydrochloric Acid from Ion Exchange Processes by Reactive Electrodialysis - Cifuentes-Molina, G (Sociedad Chilena de Quimica, 2015)
The purification process of electrolytes contaminated from electrorefining consists in placing them in contact with an ion exchange resin which can function continuously due to its reconditioning with hydrchloric acid. The treatment of the resultant solution, known as elution, consists in doing a fractional distillation releasing hydrochloric acid and gaseous chlorine. The release of these represents most of the operational problems in the electrolyte treatment plant. This paper proposes an alternative to this distillation process, using a reactive electrodialysis cell and cation and anion exchange membranes.